Sobre Finura Própria de Grafos - Sampaio Jr., Moysés S.; Oliveira, Fabiano S.; Szwarcfiter, Jayme L. (Anais do Encontro de Teoria da Computação (ETC); 2018: Anais do III Encontro de Teoria da Computação, 2018)
Both graph classes of k-thin and proper k-thin graphs have recently been introduced generalizing interval and unit interval graphs, respectively. The complexity of the recognition of k-thin and proper k-thin are open, even for fixed k ≥ 2. In this work, we introduce a subclass of the proper 2-thin graphs, called proper 2-thin of precedence. For this class, we present a characterization and an efficient recognition algorithm.